Le système Tianxia de Zhao est-il mal compris? - XU Bijun (MONDE CHINOIS NOUVELLE ASIE, 2017)
Zhao Tingyang’s Tianxia System has become a hot topic of discussion since he first introduced it during the 2005 Culture of Knowledge conference in Gao, India.1 Some commentators have spoken highly of this system as a worldview that can address problems in global development.2 Others have lodged criticisms against it.3 However, many critical commentators have an inaccurate understanding of Zhao’s theories. This paper aims to show the ways in which Zhao’s Tianxia System has been misunderstood and responds to misinterpretations of his theories.